ON THE QUESTION OF DEFINING THE CONCEPT OF ‘ARCHITECTURAL LANDSCAPE OF THE CITY’ - Loktionova, O. (Municipal economy of cities. Series: «Economy science», 2023)
The article highlights the problem of the absence of a holistic concept that could fully characterise the city. The idea of studying the city as a whole organism is not new. However, urban theories usually reveal one or several aspects, and the rest remain neglected. We used the historical-genetic and systematic methods of research and considered a few city-planning and urbanistic theories in development, showing which aspects of city life they illuminate and which remain undefined. So, we analysed the chronology of stages of the development of urban planning and drew a parallel with the sequence of the emergence of architecture, urban-planning, and urban theories. Theories demonstrating the evolution of theoretical thought from the twentieth century to the present are considered to determine the problems. Therefore, the research begins with the emergence of the concept of ‘garden city’ by E. Howard, includes the study of the formation of the concepts of districts and neighbourhoods, then the change in the concept of urban planning to urbanism, the invention of the concept of the urban environment by Glazychev, and ends with modern research on this issue. The analysis of the existing theories showed that all the proposed ones do not have a comprehensive overview and study one or several aspects without taking into account others. We identified seven core aspects of the architectural landscape of the city: geological-geographical, historical-cultural, semantic, functional, scenario, phenomenological, and social. The concept of architectural landscape combines all the listed above aspects of the study of the city. We are considering that the combination of the main aspects will avoid incompleteness and fragmentation of its understanding and will allow us to see and develop a comprehension of the life of the urban organism. Therefore, this article proposes to introduce a new concept of the architectural landscape of the city that, by forming a holistic view, would help to fill in the blank spots in modern urban theory.